(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Poverty is still a basic problem in Indonesia, as well as in Malacca Regency, East Nusa Tenggara Province (NTT). With the potential of natural resources owned by Indonesia and NTT, this should be used properly so that the national ideal as a country that has Good National Food Security. NTT and Malacca Regency have abundant natural resource potential as well, one of which is owned by Malacca Regency as a booster of the community’s economy is cassava production. However, what often becomes a problem is that cassava farmers are generally poor and require special handling efforts. Therefore, the purpose of this research is to further research how the Supply Chain Management system of cassava production in Malacca Regency. So that an ideal model of good management and management was found. The urgency of this research is important, where an ideal model of the Supply Chain Management system has been found which has the potential to be an accelerator of economic growth in the area which will boost the community’s economy. The research method used is using a mixed method approach, especially using the mixed method of sequential explanatory as described by Creswell (2014). The mixed method used in this study included three separate phases. In the initial stage, a preliminary survey was conducted to gain insight into the characteristics of the supply chain within the specified case study area, with a special focus on the Cassava commodity. The results of the research show that there are Cassava supply chain actors involving 7 main actors, namely, Farmers, Collector Traders, Small Agents, Large Agents, Retailers, Modern Markets and Consumers. The implementation of Cassava supply chain management in Malacca Regency has been running optimally because it has built an integrated relationship and good collaboration between supply chain actors from upstream to downstream, so that Cassava is distributed to consumers effectively and efficiently. Even though in terms of profits, farmers still cannot get maximum profits due to the length of the supply chain that occurs. There are three flows in the Cassava supply chain in Malacca Regency, namely the flow of goods, the flow of money, and the flow of information. The entire cassava supply chain in Malacca Regency has been running well, so that all parties can establish long-term relationships and have been well integrated to distribute to consumers.